INDOOR RADON SURVEY IN NEPAL USING PASSIVE TECHNIQUE SOLID STATE NUCLEAR TRACK DETECTOR - Buddha R, Shah; Dinesh, Thapa; Deependra D, Mulmi; Kul P, Dahal (International Journal of Clinical and Biomedical Research, 2015)
Context: It has been proved from many epidemiological studies that the inhalation of the radioactive, inert gas radon (222Rn) is the main cause of lungs cancer after smoking. Objective: The survey was conducted to estimate the indoor radon concentration, the annual effective dose rate and the annual dose equivalent rate to the lung. Material and Methods: Altogether 50 dwellings were chosen randomly at 5 different districts of Nepal. The dosimetric measurements were carried out over a period of 3 months using time-integrated passive radon detectors, CR-39 based on type II Solid State Nuclear Track Detector (SSNTD) technique. The type of houses was concrete with plastered walls and mud house. Results: The minimum concentration of radon in the study areas was found to be <20Bq.m-3 and the maximum concentration was 110±20Bq.m-3. Also the corresponding values of annual effective dose and annual equivalent dose to the lung respectively varied from <0.60 to 3.30mSv.y-1 and 0.16—10-7 to 0.88Ã—10-7 Sv.y-1. The uncertainty was measured at 95% confidence level. Conclusion: The indoor radon concentration varies considerably with the ventilation condition, lifestyle of the people, construction of the dwellings and climate of the areas. The measurements show that the radon concentrations were found to be well below the reference levels of ICRP. KEYWORDS: Indoor Radon; Annual Effective Dose; CR-39; Ventilation Condition; Dwelling.